Optimization of torsional systems with self-regulated pneumatic clutches - Segl’a, Štefan; Kalker-Kalkman, Cornelia M. (Computer Assisted Methods in Engineering and Science, 2022)
In this paper possibilities of optimization of two torsional mechanical systems with one and two differential pneumatic clutches with self-regulation are shown. The systems are excited by harmonic components of the periodic moment caused by an engine. The advantage of the differential pneumatic clutch lies in the fact that its torsional stiffness can be controlled by the pressure of a gas medium in it. Optimization of such systems enables not only minimization of vibrations and dynamic effects but also avoiding resonance regimes in relatively wide frequency intervals (speeds of rotation of the system) . As objective function the mean total amplitude of relative vibration is used. The constraints on the amplitudes of dynamic moments and also anti-resonance constraints are considered.